2020
DOI: 10.3390/s20030854
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Microcantilever Sensors to Detect the Reversible Conformational Change of a Molecular Switch, Spiropyan

Abstract: The high sensitivity of silicon microcantilever sensors has expanded their use in areas ranging from gas sensing to bio-medical applications. Photochromic molecules also represent promising candidates for a large variety of sensing applications. In this work, the operating principles of these two sensing methods are combined in order to detect the reversible conformational change of a molecular switch, spiropyran. Thus, arrays of silicon microcantilever sensors were functionalized with spiropyran on the gold c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…a tensile strain), which leads to photoactuation. This finding is perfectly in line with the results of Grogan et al 22,23 reported for silicon cantilevers grafted by a spiropyran monolayer. These authors have observed also a downward (upward) cantilever deflection upon the SP to MC (MC to SP) isomerization.…”
Section: Communicationsupporting
confidence: 93%
See 1 more Smart Citation
“…a tensile strain), which leads to photoactuation. This finding is perfectly in line with the results of Grogan et al 22,23 reported for silicon cantilevers grafted by a spiropyran monolayer. These authors have observed also a downward (upward) cantilever deflection upon the SP to MC (MC to SP) isomerization.…”
Section: Communicationsupporting
confidence: 93%
“…10%), which they attributed to the lower elastic modulus of the photoisomerized polymer film. On the other hand, Grogan et al 22,23 have functionalized gold-coated silicon microcantilevers with a spiropyran monolayer by immersing the devices into the solution of the molecules. When irradiated by UV and visible light sources the microcantilever showed a reversible deflection, which was assigned to surface stress changes induced by the photoisomerization.…”
mentioning
confidence: 99%
“…[16,44] On the other hand, opposite responses were found in the case of gold-coated silicon cantilevers decorated with the spiropyran photoswitch as a function of the location of the SAM (silicon or gold side). [17,45] Thus, the direction of the bending may depend on a multitude of factors including the cantilever material and configuration as well as the intermolecular forces within the layer and between the molecules and the transducer surface. Regarding the PDMS-MCCs, however, an accurate comparison with the reported data might be difficult to attain since polymeric cantilevers in combination with DABSYL-Cl SAMs have not been investigated before.…”
Section: Mechanochromic Response To Light-driven Molecular Conformati...mentioning
confidence: 99%
“…and bio-chemical interactions. [10,11] For instance, the structural evolutions of the molecular switches topoisomerase II, [12] bacteriorhodopsin, [13] calmodulin, [14] DNA, [15] azobenzene, [16] and spiropyran [17] have been successfully interrogated with mechanical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Another variable that can be used to quantify the amount of the adsorbed gases in the microcantilever is the change in the resonant frequency caused by the surface stresses. However, when compared to the mass loading, the effects of such stresses on the resonant frequency are found to be insignificant [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%